Analisis Peranan Efektivitas dan Kontribusi Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Bandung Periode 2017-2021 - Galang Nusantara Achmad; Brilian Noer A'la; Della Sagita Mala (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Regional tax is one of the important instruments in supporting the receipt of Regional Original Income (PAD). Therefore, every local government is required to provide efforts to optimize the collection of local taxes to the taxpayer concerned. The restaurant tax is one type of local tax that has great potential in contributing to local tax revenues. This study aims to understand and analyze the level of effectiveness and the level of contribution of restaurant tax revenues to Bandung City Original Revenue for the 2017-2021 period. This research method uses quantitative descriptive analysis techniques, so that it can be seen the level of effectiveness and the level of contribution to restaurant tax revenues in the city of Bandung. While the data obtained in the study sourced from secondary data. Based on the results and discussion, it can be concluded that the effectiveness of Bandung City restaurant tax revenue has been very effective since the last five years. This is evidenced by all levels of effectiveness showing results above 100% during the 2017-2021 period. This achievement is inseparable from the strategic potential of the Bandung City area, as well as the strategic efforts of the local government in exploring the potential and improving tax payment administration services. Meanwhile, the contribution of restaurant tax revenue to Bandung City's PAD in the last five years tends to be less contributing to PAD revenue. This is indicated by the percentage value of the contribution rate of less than 15% in each of the 2017-2021 years.